BIOM-33. TEMPORAL HETEROGENEITY OF DNA METHYLATION SUBCLASSES BETWEEN MATCHED NEWLY DIAGNOSED AND RECURRENT IDH-WILDTYPE GLIOBLASTOMA. (14th November 2022) - Drexler, Richard; Schüller, Ulrich; Eckhardt, Alicia; Sauvigny, Thomas; Ricklefs, Tammo; Bode, Helena; Khatri, Robin; Hausmann, Fabian; Hänzelmann, Sonja; Huber, Tobias; Bonn, Stefan; Lamszus, Katrin; et al.
Abstract: Spatiotemporal heterogeneity is a major factor contributing to the devastating prognosis of isocitrate-dehydrogenase (IDH )-wildtype glioblastoma. Genome-wide DNA methylation profiling allows the stratification into several DNA methylation subgroups of IDH -wildtype glioblastoma, which were shown to have a spatial heterogeneity in newly diagnosed tumors. However, the temporal heterogeneity and its clinical relevance of DNA methylation subgroups remains inconclusive. Tumor tissue obtained from first and recurrence surgery of 31 patients diagnosed with IDH -wildtype glioblastoma was subjected to DNA methylation profiling. DNA methylation profiles were analyzed for temporal heterogeneity and correlated with clinical data, survival outcome and copy number variations. In addition, deconvolution of immune cells and unsupervised hierarchical clustering using pairwise Pearson correlation coefficients of the 10.000 most variable CpG features was performed. Of all patients with matched tumor tissue, 4 (12.9%) patients had a non-matching brain tumor classifier output at recurrence. Within the remaining 27 patients, a transition of the dominant DNA methylation subclass was observed in 8 (29.6%) glioblastomas with a most frequent transition to the mesenchymal subclass (62.5%). A subclass transition was more likely after incomplete removal of contrast-enhanced tumor parts at first surgery (p = 0.04). Tumor location, adjuvant treatment, and time between primary and recurrence surgery did not influence the transition. Immune cell proportions from deconvolution data, tumor purity or specific CpG sites were not correlated with a subclass transition. Survival analyses revealed a comparable outcome for patients with or without subclass transition. Our findings demonstrate the temporal heterogeneity of DNA methylation subclasses in 29.6% of IDH -wildtype glioblastoma. We identified clinical factors and showed that a subclass transition did not impact the survival outcome. However, a possible DNA methylation subclass transition must be taken into consideration for future targeted therapies at recurrence.